Impact of posttransplant cyclophosphamide-based GVHD prophylaxis in patients 70 years and older: an update from BMT CTN 1703 - Sameem Abedin; Michael J. Martens; Javier Bolaños-Meade; Monzr M. Al Malki; Qinghua Lian; Lyndsey Runaas; Hany Elmariah; Mahasweta Gooptu; Karilyn T. Larkin; Brian C. Shaffer; Alison W. Loren; Melhem Solh; et al. (Blood Advances)
Abstract: Allogeneic hematopoietic cell transplant (allo-HCT) is underutilized in adults aged ≥70 years. Morbidity, often driven by graft-versus-host disease (GVHD), is considered a major barrier to its use. The BMT CTN 1703 trial (ClinicalTrials.gov identifier: NCT03959241) randomly assigned adults with hematologic malignancies undergoing allo-HCT after reduced intensity conditioning to receive either posttransplant cyclophosphamide, mycophenolate mofetil, and tacrolimus (PTCy) or tacrolimus and methotrexate (Tac/MTX) for GVHD prophylaxis. Overall study results revealed superior GVHD-free, relapse-free survival (GRFS) with PTCy-based prophylaxis. This analysis explored the impact of PTCy in patients aged ≥70 years enrolled in BMT CTN 1703. We analyzed outcomes for 96 patients aged ≥70 years. PTCy maintained superiority for the primary end point with a GRFS rate of 67.1% compared with 29.5% with Tac/MTX (P = .001). GVHD control and improved immunosuppression-free survival contributed to a lower 1-year nonrelapse mortality (NRM) with PTCy. Furthermore, lower rates of relapse/progression were observed with PTCy, altogether resulting in significantly improved adjusted 1-year survival with PTCy at 94.3% vs 60.2% with Tac/MTX (P = .001). PTCy-based GVHD prophylaxis should be considered standard prophylaxis for older adults. Given low rates of NRM and excellent survival outcomes with this approach, there should be greater consideration for allo-HCT in older patients, particularly patients aged ≥70 years. This trial was registered at www.ClinicalTrials.gov as #NCT03959241.